The Interaction Effect between Comorbidity Burden and Venous Thromboembolism on Mortality: A Nationwide Cohort Study - Bonnesen, Kasper; Schmidt, Morten; Horváth-Puhó, Erzsébet; Sørensen, Henrik T. (Thrombosis and Haemostasis, 2021)
Background Comorbidity influences venous thromboembolism (VTE) mortality, but it is unknown whether this is due to comorbidity alone or whether biological interaction exists.Objectives We examined whether comorbidity and VTE interact to increase VTE mortality beyond their individual effects.Methods This nationwide population-based cohort study included all VTE patients ≥18 years during 2000 to 2016, and an age-, sex-, and comorbidity-matched comparison cohort of individuals without VTE. We computed age-standardized mortality rates and examined interaction on the additive scale using interaction contrasts (difference in rate differences).Results After 30-day follow-up, the mortality rate per 1,000 person-years among individuals with no comorbidity was 419 (95% confidence interval [CI]: 391–447) in the VTE and 16 (95% CI: 13–18) in the comparison cohort (rate difference: 403). The corresponding mortality rate increased to 591 (95% CI: 539–643) in the VTE cohort and 38 (95% CI: 33–44) in the comparison cohort among individuals with low comorbidity (rate difference: 553). The interaction contrast (150) showed that 25% (150/591) of mortality was explained by the interaction in individuals with low comorbidity. This percentage increased to 56% for moderate and 63% for severe comorbidity. Interaction effects were largest within 30-day follow-up, for provoked VTE, in young individuals, and in individuals noncompliant to anticoagulant therapy. Dose–response patterns for interaction effects were also observed after 31–365-day and >1–5-year follow-up (p < 0.0001). Interaction effects varied between individual comorbidities.Conclusion Biological interaction between comorbidity and VTE explained a substantial proportion of VTE mortality. The interaction effect increased with comorbidity burden.
Keywords: comorbidity; epidemiology; interaction; mortality; venous thromboembolism